1991
DOI: 10.1148/radiology.181.3.1947108
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal tears diagnosed with MR imaging versus arthroscopy: how reliable a standard is arthroscopy?

Abstract: Arthroscopy of the menisci is considered the standard by which all noninvasive imaging procedures of the knee are measured. To better recognize the accuracy and relevance of arthroscopic correlation, a study was done in 254 consecutive patients who underwent both magnetic resonance (MR) imaging of the knee and arthroscopy. If interpretation of arthroscopic findings disagreed with MR findings, the arthroscopic videotapes were reviewed. Seventeen errors occurred in interpretation, resulting in false-positive MR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
1
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(67 citation statements)
references
References 0 publications
1
63
1
2
Order By: Relevance
“…In the same study (30), 15 of the 32 false-negative results were due to small tears which did not warrant surgical intervention. The negative predictive value of MR in double-blind studies has been reported as ranging from 80 to 100% and in other studies as between 92 and 98%.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In the same study (30), 15 of the 32 false-negative results were due to small tears which did not warrant surgical intervention. The negative predictive value of MR in double-blind studies has been reported as ranging from 80 to 100% and in other studies as between 92 and 98%.…”
Section: Discussionmentioning
confidence: 84%
“…Some false-positive results on MR investigations may reflect this. In one study (30) with 254 consecutive patients undergoing both MR imaging and arthroscopy, the videotapes from arthroscopy were reviewed in 49 patients where there was a discrepancy between the MR and arthroscopic findings. There were 17 false-positive MR interpretations of which 9 were located in the posterior horns of the menisci, areas incompletely seen on arthroscopy, and 2 were due to differences in subjective interpretation of post surgical meniscal appearances thought not to be of clinical significance at arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the acute stage following injury, clinical tests may not be appropriate due to pain, thus an MRI is the preferred modality of investigation. It is non invasive, and considered to be highly sensitive to meniscal injuries 7,8,9 but is less so for the Anterior cruciate ligament injuries. Arthroscopy of the knee is a key hole surgery performed as a daycare procedure.…”
Section: Introductionmentioning
confidence: 99%
“…An accurate description of a meniscal tear has become increasingly important, with the emphasis on meniscal preservation and repair, because of the long-term complications of meniscectomy that comprise degenerative changes, patient dissatisfaction, marked disability and chronic pain [4,11].…”
mentioning
confidence: 99%